2015
DOI: 10.3892/mmr.2015.4690
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin upregulates Nrf2 nuclear translocation and protects rat hepatic stellate cells against oxidative stress

Abstract: Abstract. The present study aimed to investigate the protective role of curcumin against oxidative stress in rat hepatic stellate cells (HSCs)-T6, and to determine the possible underlying mechanisms. HSC-T6 cells were divided into three groups: Negative control group, oxidant-treated group and curcumin-treated group. Flow cytometry and spectrophotometry were used to measure the production of reactive oxygen species (ROS), and the levels of malondialdehyde (MDA) and glutathione (GSH). Immunocytochemistry and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 52 publications
1
30
1
Order By: Relevance
“…Furthermore, chronic treatment with Cur (10-, 20- and 50-mg/kg, once daily for 8 days, peritoneally) improved the motor and cognitive performances, reduced oxidative stress, and restored succinate dehydrogenase activity, which is inhibited in the in 3-nitropropionic acid (3-NP) HD rat model. An increase in Nrf2 (a key regulator for antioxidants enzyme expression) expression in C-SLN-treated mice, compared to controls, has also been observed [ 179 ]. Cur treatment also restored the down-regulated molecular chaperones (e.g.…”
Section: Rationale For Cur Therapy In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore, chronic treatment with Cur (10-, 20- and 50-mg/kg, once daily for 8 days, peritoneally) improved the motor and cognitive performances, reduced oxidative stress, and restored succinate dehydrogenase activity, which is inhibited in the in 3-nitropropionic acid (3-NP) HD rat model. An increase in Nrf2 (a key regulator for antioxidants enzyme expression) expression in C-SLN-treated mice, compared to controls, has also been observed [ 179 ]. Cur treatment also restored the down-regulated molecular chaperones (e.g.…”
Section: Rationale For Cur Therapy In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, increasing researches have implicated that PPAR γ is a key mediator in HSC activation and phenotypic alteration, thus maintaining HSCs in a quiescent phase [ 6 , 7 ]. Recently, oxidative stress is considered to be involved in HSC activation and hepatic fibrogenesis [ 8 ]. A large amount of publications has also reported that HSCs exposed to hypoxia could be activated through HIF1 α and its downstream target genes or signaling pathways [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…At 1, 3 and 5 weeks after transplantation, the grafts (implanted Matrigel) or testicular tissues were subjected to protein extraction using RIPA lysis buffer (Solarbio) containing 1% protease inhibitors (Sangon Biotech) on ice for Western blotting analysis as previously described . Protein concentrations were normalized by the Bradford method, and 40 μg of protein per channel was subjected to 10% SDS‐PAGE and subsequently transferred to polyvinylidene difluoride membranes (Millipore).…”
Section: Methodsmentioning
confidence: 99%